Jesus as teacher in the gospel of Matthew - Quarles, Charles L.; Ridlehoover, Charles Nathan (Library of New Testament studies, 2023)
"This volume explores the means which by Matthew's Gospel provides distinctive elements of Jesus as teacher not featured in the other Gospels"--